Kotter’s 8-step change model (Henry Stewart Talks, 2025)
Kotter's Eight-Step Change Model, Change Management Pitfalls, Creating a Sense of Urgency, Building Coalitions & Change Vision, Communication Strategies for Change, Empowering Action & Removing Obstacles, Celebrating Short-Term Wins, Anchoring Change in Culture